PDMS microlenses for optical biopsy microsystems - Ribeiro, J. F. (2017)
Minimally invasive medical devices are widely investigated, because of their advantages for in-situ medical examination in real time with highly reduced risk and patient discomfort, as compared to more traditional approaches. Optical biopsy is a prominent example of this trend and provides essential diagnostic information on tissue histopathology in the gastrointestinal tract. Micro-electro mechanical system (MEMS) technology is demonstrated in this paper to be highly suitable for fabrication of an optical biopsy microsystem where overall system dimensions and power consumption are key enabling factors. The biopsy microsystem presented is 11.2 mm in diameter and 18.6 mm in length and contains an imaging system with a dedicated image magnification optical microsystem (IMOM) and light emitting diodes (LEDs). Polydimethylsiloxane (PDMS) microlenses have been fabricated using the ‘hanging droplet’ approach and integrated in the IMOM subsystem for achieving an image magnification by a factor 4 and a 30% improvement in optical irradiance from the LED illumination.